Pengaruh Ekstrak Tanaman Putri Malu (Mimosa pudica Linn) Terhadap Penurunan Kadar Glukosa Darah Pada Mencit (Mus musculus) - Mustapa, Kasmudin; Rizky, Amalia; Jura, Minarni Rama (Universitas Tadulako, 2017)
The research aim is to determine the effect of mimosa plant (mimosa pudica Linn) to reduce blood sugar levels in mice and determining the effective concentration of mimosa plant extracts as an alternative to decrease blood sugar levels. The extract is produced by the infusion method. The animal test used is male mice with amount 18 mice that induced by EDTA (ethylene diamine tetraacetic acid). Mice are divided into 6 groups randomly with different treatment. The group I, II, III and IV were given the mimosa plant extract with a concentration of 10, 20, 30, and 40% (w/v) respectively while group V is given glibenclamide suspension as positive control (+) and group VI is given Na-CMC 1% as negative control (-). Data were analyzed using the statistical test analysis of variance (ANOVA) and then followed by Duncan test. The results showed that the mimosa plant extract contains flavonoids, alkaloids, and tannins. In preclinical testing of mimosa plant extract proven to reduce blood sugar levels in mice and the most effective concentration is a concentration of 20% (w/v) with significantly Î± = 0.05.